Preschool Attention-Deficit/Hyperactivity Disorder and Telephone Medication Management at Developmental-Behavioral Pediatric Network Sites. Issue 6 (August 2021) - Harstad, Elizabeth; Shults, Justine; Barbaresi, William; Bax, Ami; Cacia, Jaclyn; Deavenport-Saman, Alexis; Friedman, Sandra; LaRosa, Angela; Loe, Irene; Mittal, Shruti; Vanderbilt, Douglas; Blum, Nathan
ABSTRACT: Objective: To understand developmental-behavioral pediatricians' (DBPs') use of clinic versus telephone encounters for preschool attention-deficit/hyperactivity disorder (ADHD) medication management. Understanding use of telephone encounters for pharmacologic management of ADHD in preschoolers may inform care for children with ADHD. Methods: DBP investigators within Developmental Behavioral Pediatrics Research Network abstracted data from medical records of 503 children aged younger than 72 months treated for ADHD with medication by a DBP clinician between January 1, 2013, and July 1, 2017, across 7 sites. We abstracted data about medication treatment episodes (defined as start and end/change of a specific type, dose, and frequency of ADHD medication) and encounter type (clinic vs telephone). We present descriptive statistics related to encounter types and χ 2 analyses to compare frequencies across reasons for the end of treatment episode and across sites. Results: The study included 503 participants with a total of 1734 treatment episodes. The initial medication was started via a clinic encounter 85.9% of the time and via telephone encounters 14.1% of the time. When evaluating reasons for end of treatment episode, decreases in dose/frequency of medication were less common for clinic versus telephone encounters (27% vs 73%; p < 0.001) and adding an additional medication was more common at clinic versus telephone encounters (64% vs 36% p < 0.001). Sites varied significantly in frequency of telephone encounters, ranging from 16.9% to 68.9% (mean 45.7%). Conclusion: Telephone encounters were used for pharmacologic management of ADHD in preschoolers to varying degrees across 7 DBP sites. These findings suggest that telephone management serves an important role in ADHD care.